DURATION OF IXODID TICK DEVELOPMENT IN SOUTHERN KHABAROVSK region - Belyaeva,N. S. (1969)
Observations on the life cycle of ixodid ticks were made in conifer-broadleaf forest near Khabarovsk between 1961 and 1965. The following species were used in the research: Haemaphysalis japonica douglasi (32 engorged females, 198 nymphs, and 595 larvae); H. concinna (22 females, 91 nymphs, and 387 larvae); Ixodes persulcatus (26 females, 171 nymphs and 1100 larvae). During the tick season, females were placed in plastic test tubes under the forest litter. Larvae and nymphs of different ages (5-320 days) reared from them were fed in the laboratory from April to October and immediately returned to the taiga. During the observation period (April till October) the average 10-day temperature of the forest litter was over 5C for 170-180 days, 10C for 130-140 days, 15C for 90-100 days, and 18C to 22C for 70-80 days (end of June to September). Trans. of Tezisy Dokl. l. Akarol. Soveshch., p31-32 1966 (sic).